1986
DOI: 10.3133/ofr86175
|View full text |Cite
|
Sign up to set email alerts
|

Geology of drill hole UE25p#1: A test hole into pre-Tertiary rocks near Yucca Mountain, southern Nevada

Abstract: Yucca Mountain in southern Nye County, Nevada, has been proposed as a potential site for the underground disposal of high-level nuclear waste. An exploratory drill hole designated UE25p#l was drilled 3 km east of the proposed repository site to investigate the geology and hydrology of the rocks that underlie the Tertiary volcanic and sedimentary rock sequence forming Yucca Mountain. Silurian dolomite assigned to the Roberts Mountain and Lone Mountain Formations was intersected below the Tertiary section betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Source data: Thordarson et al 1984 [DIRS 103200]; Rush et al 1983 [DIRS 107944];Carr et al 1986 [ 7. CONCLUSIONS…”
Section: H-3mentioning
confidence: 99%
“…Source data: Thordarson et al 1984 [DIRS 103200]; Rush et al 1983 [DIRS 107944];Carr et al 1986 [ 7. CONCLUSIONS…”
Section: H-3mentioning
confidence: 99%
“…The main strand of the fault passes along the west side of Fran Ridge. The report for borehole p#l called this the Fran Ridge fault (Carr et al 1986b, Figure 12) and indicated that it intersects borehole p# 1 at the Tertiary-Paleozoic unconformity. This is the interpretation used to construct the Paintbrush Canyon fault in the GFM.…”
Section: Features Of Individual Faultsmentioning
confidence: 99%
“…At the depths indicated, a large volume of magnetic material is required to explain the magnetic high. Therefore, a granitic intrusion or batholith is more likely to be the primary source, perhaps with some contribution from magnetized argillite (Kane and Bracken, 1983;Carr and others, 1986;Oliver, Ponce, and Blank, 1995).…”
Section: Other Domainsmentioning
confidence: 99%